Ductile fracture in metal forming : modelling and simulation - Komori, Kazutake (Academic Press is an imprint of Elsevier, 2020)
Ductile Fracture in Metal Forming provides an approach to micromechanical ductile fracture prediction which is applicable to all metal-forming processes. It also examines, in detail, our current understanding of the mechanics and physics of ductile fracture in metal-forming processes. Starting with an overview of different ductile fracture scenarios, this book goes on to explain modeling techniques that predict a range of mechanical phenomena that can lead to ductile fracture. The particular challenges in creating micromechanical models are addressed, as are methods of applying these models to several common metal-forming processes.